Construction of Feminine Identities in the Works of Marquez - Saman, Attia (International Journal of Psychosocial Rehabilitation, 2020)
Magic realism offers to the writers wishing to write against totalitarian regimes as a means to attack such systems and question the definitions upon which these systems rely (Bowers 04). Magic realism is an appropriate mode to exhibit real conditions of women in this patriarchal society for male and female authors. The research aims to analyze selected texts written by Garcia Marquez. The analysis of the texts has been intended to understand feminism and help to redefine our ideas about power and women and show how power is unfixed and unstable. For the purpose of the research a deconstructive analysis of the texts has been taken up. I will analyze the texts on two levels to reveal the ways through which Marquez has shown women’s concerns as powerful, not as pointless and superficial waste of time. Secondly, the research will highlight the ways through which magic realist texts rework upon old and tried stereotypes of evil woman and offer alternatives to imagine ways of being a woman which include all the possible positions. The texts selected for the study reveal a wide variety of women from high class powerful women, to highly rebellious. The characters of the text range from self-identified to those who would rather remain introvert.